Contextualization of Hadith. To Oppose the Patriarchy and Dehumanization in Building the Civilization of Gender in Islam - (Damanhuri), Damanhuri (Italian Sociological Review, 2018)
The thought about women’s participation in building a civilization of mankind do not only affect in the political field, but also in the domestic and some aspects of human life. Women should not be placed in undertaken side, so that if they are ineligible to control and determine the direction of development of the state and the nation. Women should play an active role alongside men to build the country into an ample effort to achieve progress in various aspects of life, economic, political, social and cultural. In this issue, it was the scientists’ discovery for admitted, but on one-sided of other existing discoveries, the authors are also dominated by men and the textual approach has gained strength in understanding the Prophet says. This article concludes that the cause of patriarchal attitudes and dehumanization is the bias of the rigid textual approach.